2023
DOI: 10.3390/diagnostics13101684
|View full text |Cite
|
Sign up to set email alerts
|

CBCT for Diagnostics, Treatment Planning and Monitoring of Sinus Floor Elevation Procedures

Abstract: Sinus floor elevation (SFE) is a standard surgical technique used to compensate for alveolar bone resorption in the posterior maxilla. Such a surgical procedure requires radiographic imaging pre- and postoperatively for diagnosis, treatment planning, and outcome assessment. Cone beam computed tomography (CBCT) has become a well-established imaging modality in the dentomaxillofacial region. The following narrative review is aimed to provide clinicians with an overview of the role of three-dimensional (3D) CBCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 125 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…In the present research, we obtained 6 months postoperative volumes corresponding to the quantity of xenograft material used for recontouring the lack of native bone. We, therefore, highlight the utility of performing CBCT evaluations of the grafted sites to properly evaluate the stability of the results, as sustained in most recent studies [ 38 ] and to exclude any pathology that might affect the outcome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present research, we obtained 6 months postoperative volumes corresponding to the quantity of xenograft material used for recontouring the lack of native bone. We, therefore, highlight the utility of performing CBCT evaluations of the grafted sites to properly evaluate the stability of the results, as sustained in most recent studies [ 38 ] and to exclude any pathology that might affect the outcome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The image of the upper limit of the biomaterial was assessed two-dimensionally in the panoramic radiograph, as a mesio-distal aspect. Although the CBCT produces a more accurate three-dimensional image, its use is not justified without the suspicion of a pathology due to the higher radiation dose [18,19]. Panoramic radiography is necessary anyway before the insertion of the implants, after the osseointegration period and several years after the end of the treatment at a routine check-up.…”
Section: Discussionmentioning
confidence: 99%
“…Transalveolar technique for sinus floor elevation requires sufficient bone mass, otherwise it can increase the probability of mucosal perforation. It is recommended that the least bone mass is 5mm below the sinus floor [1]. The World Dental Federation (FDI) has suggested that the recommended bone mass for transalveolar technique is at least 6mm.…”
Section: Types Of Maxillary Sinus Elevationmentioning
confidence: 99%